2011
DOI: 10.1111/j.1365-2826.2011.02120.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Aromatase Gene Expression in the Medaka Brain

Abstract: The brain of teleost fish exhibits a significant degree of sexual plasticity, even in adulthood. This unique feature is almost certainly attributable to a teleost-specific sexual differentiation process of the brain, which remains largely unknown. To dissect the molecular basis of sexual differentiation of the teleost brain, we searched for genes differentially expressed between both sexes in the medaka brain. One gene identified in the screen, cyp19a1b, which encodes the steroidogenic enzyme aromatase, was se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 64 publications
2
55
1
Order By: Relevance
“…Data recently obtained in our laboratory demonstrated that in amphibian, aromatase expression is restricted to neurons during development as in adulthood [81]. In adult zebrafish, we did not observe sexual dimorphism in the expression of AroB (transcripts and protein) while in medaka, females exhibit a stronger periventricular expression in several regions, in particular the optic tectum [73].…”
Section: Aromatase and Radial Glial Cellscontrasting
confidence: 51%
See 1 more Smart Citation
“…Data recently obtained in our laboratory demonstrated that in amphibian, aromatase expression is restricted to neurons during development as in adulthood [81]. In adult zebrafish, we did not observe sexual dimorphism in the expression of AroB (transcripts and protein) while in medaka, females exhibit a stronger periventricular expression in several regions, in particular the optic tectum [73].…”
Section: Aromatase and Radial Glial Cellscontrasting
confidence: 51%
“…The small number of labeled cells and the fact that this antibody was raised against human aromatase now suggest that these results were artifactual. Since Forlano et al work until the most recent publications in fish [71], the development of homologous and specific molecular tools such as cyp19a1b riboprobes and AroB antibodies has revealed in many teleost species a high number of AroB-expressing cells in ventricular position in the forebrain and midbrain, consistent with the strong aromatase enzymatic activity [64,68,[71][72][73]. In zebrafish, cyp19a1b messengers are strongly expressed along the ventricles in the olfactory bulbs, telencephalon, preoptic area, hypothalamus, thalamus and optic tectum [74].…”
Section: Aromatase and Radial Glial Cellsmentioning
confidence: 68%
“…We presume that the sexual dimorphism of cyp19a1b certainly influence brain sex differentiation because of its ability to 'estrogenize' the brain (Table 1). Interestingly, in the Japanese medaka, it is not until before the onset of puberty that cyp19a1b expression is sexually differentiated (Okubo et al, 2011; Table 1). It is also documented that cyp19a1b is a target for xenoestrogens in the same species (Kuhl et al, 2005; Table 1).…”
Section: Brain Aromatase Cyp191a1bmentioning
confidence: 98%
“…cyp19a1b, GTHs Kuhl et al (2005) cyp19a1b triggers abnormal sex differentiation in xenoestrogens treated fish Patil and Gunasekera (2008) cyp19a1b contributes for neural development and possibly sexual behavior and found at high levels in adult female brain Okubo et al (2011) Female biased expression of cyp19a1b Weltzien et al (2013) Slow/late origin of gonadotrope cells and GTHs 13…”
Section: Sbgnrh Sgnrh and Gnrh Receptormentioning
confidence: 99%
“…The sections were digested with proteinase K (Wako Pure Chemical Industries, Osaka, Japan) for 15 min at 378C, postfixed with 4 per cent PFA for 10 min, and acetylated with 0. 25 (d) Examination of genetic and phenotypic sex dependence of ER and AR expression Sex-inverted medaka were produced as described previously [14]. Briefly, fertilized eggs were incubated at high temperature (328C) and simultaneously received 0.2 ng ml 21 methyltestosterone until hatching, which led to the production of XX males.…”
Section: (A) Animalsmentioning
confidence: 99%